Population pattern and social change in India. - Chandra, Sharat (Allahabad, 1991)
The book contains chapters with all cohesion and correlation. The first chapter deals with the introductory part. The second one covers the geographical background and setting. An in-depth analysis of spatial patterns of population mobility in and outside the area under study has been made in the subsequent chapter. After dealing with the types & factors of migration, dynamics of rural-urban migration has been studied in detail.
Keywords: Population